TEACHER IDENTITY AND TRANSNATIONAL EXPERIENCE: ACASE OF AN EFL TEACHER FROM GEORGIA TEACHING INTURKEY - (:unkn) unknown (My University, 2017)
0

The article presents a case study of an experienced non-native EFL teacher with educational background and teaching experience from her home country Georgia, and with a present EFL teaching position in her host country Turkey. Based on interview and graphic elicitation data, the study explored the changes which her teacher identity had undergone after interaction between her Georgian background and new Turkish context. These changes were investigated from social constructivist perspective in terms of culture, professional development, reflectivity, motivation, theory-practice integration and collaboration. Data were analyzed through structural, in vivo, open and theory-driven coding. The results indicated three main changes involving the following themes: (1) intercultural competence, (2) teacher development, and (3) collaboration. These transformations were identified with the development of three sub-identities respectively: intercultural, professional and social. The findings are consistent with multifaceted and dynamic nature of teacher identity. As for implementations, transnational teaching experience should be fostered by institutions and intercultural competency should be integrated into teacher education disciplines.
Keywords: Eğitim, Eğitim Araştırmaları